Annual Report on surveillance for avian influenza in poultry and wild birds in Member States of the European Union in 2018. (19th December 2019) - ,; Brouwer, Adam; Gonzales, Jose; Huneau, Adeline; Mulatti, Paolo; Kuiken, Thijs; Staubach, Christoph; Stegeman, Arjan; Antoniou, Sotiria‐Eleni; Baldinelli, Francesca; Van der Stede, Yves; Aznar, Inma
Abstract: Avian influenza (AI) is a viral infectious disease that affects all species of domestic and wild birds. The viruses causing this disease can be of high (HPAI) or low (LPAI) pathogenicity and represent a continuous threat to poultry in Europe. Council Directive 2005/94/EC requests EU Member States (MSs) to carry out surveillance in poultry and wild birds and notify the results to the responsible authority. Therefore, MSs and Switzerland have implemented surveillance programmes to yearly monitor incursions of AI viruses in poultry and wild birds. EFSA received a mandate from the European Commission, to collate, validate, analyse and summarise in an annual report the data resulting from the avian influenza surveillance programmes. This is the first report produced under this mandate summarising the results of the surveillance activities carried out in poultry and wild birds in 2018. Overall 18, 596 poultry establishments were sampled, of which 43 were seropositive for H5 AI and two for H7 AI. Seropositive establishments were found in 11 MSs, with the highest percentage of seropositive establishments being found in waterfowl gamebird, and geese and duck breeding establishments. A total of 9, 145 dead/moribund wild birds were sampled, with 163 birds testing positive to HPAI virus H5N6. The infected birds were reported by eight MSs and were mostly found between January and April 2018. In this report, the wild bird species affected with HPAI are described and the strategy of targeted sampling is assessed. The crude odds ratio of HPAI detection as a function of the target species (species belonging to the list of target species versus species not belonging to the target list) is presented. The surveillance findings for poultry and wild birds for 2018 are also discussed in relation to findings from previous years and current knowledge on the epidemiology of AI in Europe.